Analisis Dinamika IK-CEPA (Indonesia-Korea Comprehensive Economic Partnership Agreement) pada Sektor Ekonomi di Indonesia - Ichabell Arkanza Umarsyah; Intan Kinanthi Damarin Tyas; Anita Shalehah (Universitas Wahid Hasyim Semarang, 2026)
Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA) is a bilateral agreement aimed at strengthening economic cooperation between the two countries. However, its development has exhibited considerable complexity, from the negotiation stage to implementation. This study aims to analyze the dynamics of IK-CEPA on Indonesia’s economic sectors using a descriptive qualitative approach through a literature review method. The analysis employs the theory of international economic cooperation to examine the economic relationship between Indonesia and South Korea, as well as the two-level game theory to explain the dynamics of IK-CEPA, which reflect the interplay between domestic and international factors in the negotiation process. The results indicate that IK-CEPA has experienced fluctuating dynamics across the phases of negotiation, ratification, and implementation. The agreement has contributed to increased investment, export diversification, and economic integration, although it still faces technical challenges and varying levels of readiness among business actors.